2023
DOI: 10.22207/jpam.17.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant and Methicillin Sensitive Staphylococcus aureus Nasal Carriage and their Antibiotic Resistant Patterns in Kirkuk City, Iraq

Abstract: The carriage of community-acquired methicillin-resistant S. aureus (CA-MRSA) has become a source of community-associated infections, particularly in the anterior nares of people worldwide. This study was aimed at determining the prevalence of community-acquired S. aureus (CA-SA) and CA-MRSA nasal carriage among healthy individuals of various ages in Kirkuk City and evaluating the susceptibility of isolates to various antibiotics. A total of 597 healthy individuals were recruited in the community between Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
1
Order By: Relevance
“…The overall resistant rates, against different antibiotics used in this study, were relatively compatible with those reported by Abdulqader and Saadi (2019) in Erbil city, who reported a relatively high resistant rates (20-60%) of S. aureus isolates including MRSA to the majority of the antibiotics used. However, the multidrug resistance rate (57.5%) reported in the current study was almost doubled comparing with the multidrug resistance of S. aureus isolates (33.3%) reported by AL-Salihi et al, (2023) in Kirkuk city, Iraq. The prevalence of MRSA is still used to gauge the proper use of antibiotics as well as effective infection control and prevention techniques.…”
Section: Discussioncontrasting
confidence: 64%
“…The overall resistant rates, against different antibiotics used in this study, were relatively compatible with those reported by Abdulqader and Saadi (2019) in Erbil city, who reported a relatively high resistant rates (20-60%) of S. aureus isolates including MRSA to the majority of the antibiotics used. However, the multidrug resistance rate (57.5%) reported in the current study was almost doubled comparing with the multidrug resistance of S. aureus isolates (33.3%) reported by AL-Salihi et al, (2023) in Kirkuk city, Iraq. The prevalence of MRSA is still used to gauge the proper use of antibiotics as well as effective infection control and prevention techniques.…”
Section: Discussioncontrasting
confidence: 64%